2019
DOI: 10.1093/eurheartj/ehz068
|View full text |Cite
|
Sign up to set email alerts
|

Altered limbic and autonomic processing supports brain-heart axis in Takotsubo syndrome

Abstract: Aims Takotsubo syndrome (TTS) is characterized by acute left ventricular dysfunction often triggered by emotional or physical stress. Severe activation of the sympathetic nervous system with catecholamine release caused by a dysfunctional limbic system has been proposed as a potential mechanism. We hypothesize that brain regions responsible for autonomic integration and/or limbic processing might be involved in the development of TTS. Here, we investigated alterations in resting state functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(109 citation statements)
references
References 23 publications
6
99
0
4
Order By: Relevance
“…Specifically, patients with TTS had a cortex over the limbic region and significantly reduced connectivity in the autonomic nervous system, including the left amygdala, both hippocampi, the left superior temporal pole, and right putamen [47]. Moreover, a recently published study similarly reported reduced functional connectivity in the limbic systems of patients with TTS patients relative to healthy individuals [48]. As noted above, the proportion of individuals with mental disorders was found to be higher among patients with TTS than in a general population.…”
Section: Brain-heart Connection In Takotsubo Syndromementioning
confidence: 93%
“…Specifically, patients with TTS had a cortex over the limbic region and significantly reduced connectivity in the autonomic nervous system, including the left amygdala, both hippocampi, the left superior temporal pole, and right putamen [47]. Moreover, a recently published study similarly reported reduced functional connectivity in the limbic systems of patients with TTS patients relative to healthy individuals [48]. As noted above, the proportion of individuals with mental disorders was found to be higher among patients with TTS than in a general population.…”
Section: Brain-heart Connection In Takotsubo Syndromementioning
confidence: 93%
“…In total, 50% of patients with TS suffer from an acute or chronic neurological or psychiatric disease [4], which suggests that the brain may be a critical component during pathogenesis. A recent study showed characteristic activity of brain regions in functional MRI [47], which may be the basis for future research to identify specific changes of regional brain function potentially inducing myocardial stunning. As outlined above, a "humoral" hypothesis postulates that circulating catecholamines, sex hormones, and others finally induce or trigger TS.…”
Section: Spasm Catecholamines Gender and The Brainmentioning
confidence: 97%
“…The brain-heart interaction has been long acknowledged as a significant factor for various cardiovascular diseases (15). Overstimulation of the sympathetic nervous system due to physical or emotional stressors has been hypothesized as the underlying cause of myocardial infarction, hypertension, arrythmias and stress induced/Takotsubo cardiomyopathy (15)(16)(17).…”
Section: Cardiologymentioning
confidence: 99%